1998
DOI: 10.1128/jvi.72.5.4265-4273.1998
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Postinoculation ( R )-9-(2-Phosphonylmethoxypropyl)Adenine Treatment for Prevention of Persistent Simian Immunodeficiency Virus SIV mne Infection Depends Critically on Timing of Initiation and Duration of Treatment

Abstract: (R)-9-(2-Phosphonylmethoxypropyl)adenine (PMPA), an acyclic nucleoside phosphonate analog, is one of a new class of potent antiretroviral agents. Previously, we showed that PMPA treatment for 28 days prevented establishment of persistent simian immunodeficiency virus (SIV) infection in macaques even when therapy was initiated 24 h after intravenous virus inoculation. In the present study, we tested regimens involving different intervals between intravenous inoculation with SIV and initiation of PMPA treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
8

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(116 citation statements)
references
References 30 publications
7
101
0
8
Order By: Relevance
“…1 and refs 7,9,14,15). Although these pathological changes occur over many years, studies in NHPs show that immunological [16][17][18][19] and anti-retroviral interventions 5 very early in infection have lasting and profound effects on post-infection control of viraemia, even if the intervention is transient. 5,16,17 This is also consistent with the relationship between peak viraemia early in HIV infection and viral set-point later in infection.…”
Section: Course Of a Typical Untreated Hiv Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 and refs 7,9,14,15). Although these pathological changes occur over many years, studies in NHPs show that immunological [16][17][18][19] and anti-retroviral interventions 5 very early in infection have lasting and profound effects on post-infection control of viraemia, even if the intervention is transient. 5,16,17 This is also consistent with the relationship between peak viraemia early in HIV infection and viral set-point later in infection.…”
Section: Course Of a Typical Untreated Hiv Infectionmentioning
confidence: 99%
“…1 As indicated above, the first 24 to 72 hr after exposure includes the window of opportunity when acquisition can be blocked. 5 Its outer limit is establishment of the resting memory CD4 + T-cell reservoir, which no known intervention has depleted (reviewed in ref. 28).…”
Section: Fiebig Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal studies, the administration of HIV PEP was most beneficial at reducing or eliminating viral replication when initiated within 24 hours of an exposure, with the most beneficial time frame for initiating prophylaxis being within 1 to 2 hours of an exposure (Otten et al, 2000;Tsai et al, 1998;Wick & Self, 2000). Based on the data collected from these animal studies, HIV PEP should be initiated as soon as possible following a potential exposure.…”
Section: Time Frame For Initiating Hiv Pepmentioning
confidence: 99%
“…In a study conducted by Otten et al (2000), the administration of a single antiretroviral agent for 28 days prevented subsequent seroconversion of all exposed animals. In a study by Tsai et al (1998) different intervals between HIV exposures and initiation of antiretroviral medications and different durations of antiretroviral therapy as it relates to the ability to prevent subsequent HIV seroconversion were evaluated. The study revealed postexposure prophylaxis begun within 24 hours of the initial exposure and continued for 28 days was the most beneficial in preventing seroconversion.…”
Section: Hiv Pep Medication Regimesmentioning
confidence: 99%